Hadis Tentang Dialog Antaragama: Membangun Jembatan Antara Komunitas Muslim dan Non-Muslim - Siregar, Lil Sapnur Aspin (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
This study aims to analyze and explore relevant hadiths in promoting interfaith dialogue, especially in building harmonious relations between Muslim and non-Muslim communities. By focusing on the aspects of tolerance, respect for other beliefs, and peaceful coexistence, this study examines the role of hadith as a guide in promoting constructive dialogue. The methodology used is a qualitative approach with a library research method, which involves an in-depth analysis of hadith books and the works of classical and contemporary scholars' interpretations related to social and interfaith interactions. The results of the study show that the Prophet Muhammad gave a real example in establishing good communication with non-Muslim communities, such as his interactions with Jews and Christians in Medina. Several hadiths emphasize the importance of respecting differences and rejecting violence, which are in line with the values ​​of pluralism. The conclusion of this study is that hadith can serve as a theological foundation for promoting interfaith dialogue, thus opening up opportunities for the creation of more inclusive and harmonious relations between Muslims and non-Muslims. This study makes an important contribution in the contemporary context, where global challenges related to religious conflicts increasingly require a dialogical approach based on Islamic teachings.